STUDIES ON VIABILITY OF BACTERIAL BIOAGENTS FORMULATION IN VACUUM PACKING COMPARED TO CONVENTIONAL PACKING (Journal of Plant Disease Sciences, 2025)
The shelf life and viability of bacterial bioagents like Pseudomonas and Bacillus species are significantly influenced by factors such as formulation, moisture content, and resilience to adverse climatic conditions. Numerous commercial formulations of Pseudomonas and Bacillus species are widely available and commonly used for the management of soil-borne plant diseases. Understanding the optimal storage conditions is essential for maintaining a high number of viable propagules over time. This study found that vacuum packing did not provide any significant advantages over conventional packaging methods. Moreover, storing the bioagents in a refrigerator at 4 °C proved to be more effective than other storage conditions such as room temperature (27 ± 2 °C), incubator (24 ± 2 °C), and deep freezer (-20 °C).
Keywords: Viability; Bioagents; Packaging; Storage